Incremental dialysis for preserving residual kidney function—Does one size fit all when initiating dialysis?. Issue 4 (7th May 2018) - Mathew, Anna T.; Obi, Yoshitsugu; Rhee, Connie M.; Chou, Jason A.; Kalantar‐Zadeh, Kamyar
Abstract: While many patients have substantial residual kidney function (RKF) when initiating hemodialysis (HD), most patients with end stage renal disease in the United States are initiated on 3‐times per week conventional HD regimen, with little regard to RKF or patient preference. RKF is associated with many benefits including survival, volume control, solute clearance, and reduced inflammation. Several strategies have been recommended to preserve RKF after HD initiation, including an incremental approach to HD initiation. Incremental HD prescriptions are personalized to achieve adequate volume control and solute clearance with consideration to a patient's endogenous renal function. This allows the initial use of less frequent and/or shorter HD treatment sessions. Regular measurement of RKF is important because HD frequency needs to be increased as RKF inevitably declines. We narratively review the results of 12 observational cohort studies of twice‐weekly compared to thrice‐weekly HD. Incremental HD is associated with several benefits including preservation of RKF as well as extending the event‐free life of arteriovenous fistulas and grafts. Patient survival and quality of life, however, has been variably associated with incremental HD. Serious risks must also be considered, including increased hospitalization and mortality perhaps related to fluid and electrolyte shifts after a long interdialytic interval. On the basis of the above literature review, and our clinical experience, we suggest patient characteristics which may predict favorable outcomes with an incremental approach to HD. These include substantial RKF, adequate volume control, lack of significant anemia/electrolyte imbalance, satisfactory health‐related quality of life, low comorbid disease burden, and good nutritional status without evidence of hypercatabolism. Clinicians should engage patients in on‐going conversations to prepare for incremental HD initiation and to ensure a smooth transition to thrice‐weekly HD when needed.